2021
DOI: 10.3389/fonc.2021.593996
|View full text |Cite
|
Sign up to set email alerts
|

Image-Guided Peri-Tumoral Radiofrequency Hyperthermia-Enhanced Direct Chemo-Destruction of Hepatic Tumor Margins

Abstract: PurposeTo validate the feasibility of using peri-tumoral radiofrequency hyperthermia (RFH)-enhanced chemotherapy to obliterate hepatic tumor margins.Method and MaterialsThis study included in vitro experiments with VX2 tumor cells and in vivo validation experiments using rabbit models of liver VX2 tumors. Both in vitro and in vivo experiments received different treatments in four groups (n=6/group): (i) RFH-enhanced chemotherapy consisting of peri-tumoral injection of doxorubicin plus RFH at 42°C; (ii) RFH alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The VX2 tumor was propagated by the transplanted tumor of the rabbit model, which were left based on our previous research and stored in liquid nitrogen, and the orthotopic models of liver tumors were also established as our previously reports [ 18 , 41 ]. Briefly, 31 male New Zealand white rabbits (2–2.5 kg in weight) were prepared, and one was the donor rabbit and the other thirty were the intervention ones.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The VX2 tumor was propagated by the transplanted tumor of the rabbit model, which were left based on our previous research and stored in liquid nitrogen, and the orthotopic models of liver tumors were also established as our previously reports [ 18 , 41 ]. Briefly, 31 male New Zealand white rabbits (2–2.5 kg in weight) were prepared, and one was the donor rabbit and the other thirty were the intervention ones.…”
Section: Methodsmentioning
confidence: 99%
“…Hyperthermia has also been confirmed to improve the anti-tumor efficacy of chemotherapeutic drugs by increasing the delivery efficiency and distribution [ 17 ]. Our previous studies have also shown that radiofrequency hyperthermia can improve the distribution of chemotherapy drugs in the tumor and enhance the killing effect of tumor cells [ 18 ]. Therefore, if hyperthermia can be introduced into the existing chemoembolization treatment system, it will significantly improve the efficacy of TACE treatment.…”
Section: Introductionmentioning
confidence: 99%
“…CdSe/Fe3O4 nanoplatforms coated with multi-mode polymers had both optical and magnetic functions [128,129]. They co-wrapped with CdSe quantum dots and Fe3O4-NPs, and it was demonstrated for the first time that they may have biomedical applications based on two-photon and magnetothermal therapies such as Extensive studies have shown that thermotherapy is an effective sensitizer of tumor chemoresistancy, which can greatly improve the effectiveness of chemotherapy [130] and enhance the antitumor effect of chemotherapeutic agents [131]. Therefore, the introduction of hyperthermia into the chemoembolization system could significantly improve the efficacy of transcatheter arterial chemoembolization (TACE).…”
Section: Metabolism Modulation By Heat Stressmentioning
confidence: 99%
“…Based on these findings we sought to develop a new approach, to simultaneously deliver oncolytic therapeutics to the tumor periphery during thermal ablation. This novel concept combines RFA-associated RFH, i.e., combining usual thermal ablation with lethal heat (>60°C) destroying tumor cells in the tumor center, with peri-tumoral specific delivery of high-dose oncolytic therapeutics to further kill tumor cells within the difficult to treat periphery of the ablated tumors ( 24 , 25 ). Thus, this innovative synergistic combination could ensure complete eradication of all viable tumor cells in and adjacent to the tumor being treated, while sparing adjacent normal structures.…”
Section: Introductionmentioning
confidence: 99%